Curug Cipamingkis Strategy as a Leading Travel Destination in Kesatuan Pemangkuan Hutan (KPH) Perhutani Bogor - Putri, Nurazahra Dwi (UI Scholars Hub, 2024)
This research discusses the promotion strategy for the Cipamingkis Waterfall as a famous destination at the Kesatuan Pemangku Hutan (KPH) Perhutani Bogor with the aim of knowing how to promote Cipamingkis Waterfall in utilizing its tourism potential. This research was conducted when the author did an internship for 3 months. The research method used is descriptive qualitative with data collection techniques based on observations, interviews with managers, conducting direct surveys to destinations and literature studies or literature studies according to the theme. The results from the promotional strategy carried out by Cipamingkis Waterfall are quite good and must be maintained, starting from the use of various social media such as Instagram, Tiktok, and official websites, the use of print media such as distributing brochures, introducing good destinations to schools, agencies and groups. nature lovers, installation of banners and banners. The author advises and recommends to the Manager of Cipamingkis Waterfall to optimize promotions in order to introduce destinations widely and can increase tourist visits to Cipamingkis Waterfall, Bogor.